2016
DOI: 10.1016/j.ijmecsci.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of micro flexible rolling with consideration of material heterogeneity

Abstract: This paper establishes a finite element model to numerically study the springback in thickness direction during micro flexible rolling process, in which 3D Voronoi tessellation has been applied to describe grain boundary and generation process of grain in the workpiece. To reflect material heterogeneity, nine kinds of mechanical properties defined by nine types of heterogeneity coefficients are selected and assigned to Voronoi polyhedrons as per the statistical distribution of hardness of grains identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The Newton-Raphson iterations were subsequently performed within an increment step to acquire the equilibrium condition between the externally applied load and the internal structural resistance [21]. The scheme is given by…”
Section: Solution Methodsmentioning
confidence: 99%
“…The Newton-Raphson iterations were subsequently performed within an increment step to acquire the equilibrium condition between the externally applied load and the internal structural resistance [21]. The scheme is given by…”
Section: Solution Methodsmentioning
confidence: 99%
“…It is found that the average springback shows a decreasing trend with the increase of front and back tensions in case of micro flexible rolling of ultrathin aluminium alloy strips. For strips with thickness values of 100, 250 and 500 μm, more front and back tensions play a more crucial role in eliminating the springback despite the change of reduction [4].…”
Section: Size Effects In Micro Flexible Rollingmentioning
confidence: 99%
“…In micro ultrathin strip rolling, the width and thickness of the strip being rolled are normally in the domains of lower millimetre and submillimetre, respectively. With the development of rolling and microforming technology, other micro rolling methods, including micro flexible rolling [3,4] and micro cross wedge rolling [5], have also been successfully developed.…”
Section: Introductionmentioning
confidence: 99%
“…grain size and temperature), a discrete distribution instead of a superposition of flow stress curves was observed due to the grain heterogeneity in micro scale. The scatter of flow stresses obtained from experiments reflects the inhomogeneous material behaviour in microforming [33,37]. Therefore, the scatter of flow stress was used to represent grain heterogeneity in this study.…”
Section: Finite Element Modelling Of Micro Compressionmentioning
confidence: 99%